Can the Other be Heard? Response to Commentaries on ‘Omphile and his Soccer Ball’ - Ndhlovu, Finex (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
I welcome the invitation to a right of reply that Multilingual Margins journal has extended to me; and I thank all nine discussants for sharing their thoughts on my paper ‘Omphile and his soccer ball: Colonialism, methodology, translanguaging research’.